Erratum: Fox, E.G.P et al. (2007) On the immature stages of the crazy ant Paratrechina longicornis (Latreille 1802) (Hymenoptera: Formicidae). Zootaxa, 1503, 1-11. - Fox, E. G. P. (Zootaxa, 2008)
(Erratum)